Pengaruh Terapi Meditasi Pernapasan Terhadap Tingkat Stress Penderita Kekambuhan Gastritis Pada Dewasa Awal Di Lingkungan Rw 001 Ragamukti Tarjurhalang Bogor Tahun 2023 - Muhammad Eka Jaya Maualana; Elvie Tresya; Indri Sarwili (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Stress in patients with gastritis recurrence is a physiological problem felt by early adults when they experience relapses of gastritis. Management of stress in patients with gastritis recurrence in early adulthood can be overcome with complementary therapy, namely breathing meditation therapy. Breathing meditation therapy itself is an activity that aims to achieve mental calm by focusing your breathing so you can relax your mind and body. This study aims to determine the effect of providing breathing meditation therapy on the stress levels of patients with gastritis recurrence in early adulthood in the Rw 001 Ragamukti Tajurhalang Bogor environment. In this research, the method used is pre-experimental quantitative research with a one group pretest – posttest design. The sample consisted of 15 early adults suffering from recurrent gastritis in the Rw 001 Tajurhalang Bogor area who were selected using a purposive sampling technique using a questionnaire with a Likert measuring scale. This research uses the Wilcoxon Signed Rank test with a significant value of α=(<0.05). The test results from this research were that most respondents experienced a decrease in stress levels as evidenced by the presence of a percentage in the mild stress range of 9 people (60.0%), while respondents who experienced moderate levels of stress were 6 people (40.0%) with an average value of The average (mean) stress level after receiving breathing meditation therapy was 8.47. Indicating that the ρ value = <.001, where the ρ value was less than 0.05, so the null hypothesis (H0) was rejected, so the alternative hypothesis was accepted (Ha).